Ecosystem services research in Latin America: the state of the art - Balvanera, Patricia; Uriarte, M.A; Almeida-Lenero, L.; Altesor, A.; DeClerck, Fabrice A.J. (Elsevier, 2012)
Ecosystem services science has developed at a fast rate in Latin America, a region characterized by a high biological and cultural diversity, strong emphasis in foreign investment, and high socioeconomic inequities. Here we conducted the following analyses at the regional and national scales: (1) how and when did the study of ecosystem services arise in each country?, (2) what is our present understanding of ecosystem service supply, delivery to societies, and social and economic values?, (3) what is the state of the art in integrating tradeoffs among services and in using interdisciplinary perspectives?, and (4) how has ecosystem service research been connected to policy design or management for sustainability? A large literature review (>1000 references) showed that in Latin America ES supply and links to policy have been the most frequently assessed. Overall, emphasis has been placed on a few services, namely carbon and water. Payments for ecosystem services have received considerable attention in the region, though with strong differences across nations and with important limitations in their application. The future of the ecosystem service paradigm in Latin America will largely depend on its capacity to demonstrate effectiveness in meeting both conservation and development goals.